2010
DOI: 10.1212/wnl.0b013e3181fd633d
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual reasoning predicts handwriting impairments in adolescents with autism

Abstract: Background:We have previously shown that children with autism spectrum disorder (ASD) have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 6 publications
2
36
3
3
Order By: Relevance
“…The same study found that visual perceptual ability was only moderately correlated with handwriting legibility in children with ASD Cartmill et al (2009). In similar light, Fuentes et al (2010) reported that while adolescents with ASD did not differ significantly from their typically developing peers on a test of perceptual reasoning, this ability was predictive of handwriting performance. This correlation may be related to the ability of the children to learn strategies to compensate for motor impairments (for example, forming letters in a piecemeal fashion) (Fuentes et al 2010).…”
Section: Visual Perceptionmentioning
confidence: 87%
See 4 more Smart Citations
“…The same study found that visual perceptual ability was only moderately correlated with handwriting legibility in children with ASD Cartmill et al (2009). In similar light, Fuentes et al (2010) reported that while adolescents with ASD did not differ significantly from their typically developing peers on a test of perceptual reasoning, this ability was predictive of handwriting performance. This correlation may be related to the ability of the children to learn strategies to compensate for motor impairments (for example, forming letters in a piecemeal fashion) (Fuentes et al 2010).…”
Section: Visual Perceptionmentioning
confidence: 87%
“…Fuentes et al (2010) also reported that adolescents with ASD performed more poorly than their typically developing peers on spacing. The effect of instructional cues (for example, use of lined paper) on these measures is unclear.…”
Section: Alignment Spacing and Sizingmentioning
confidence: 95%
See 3 more Smart Citations